The Influence of Human Capital and Organizational Culture on Staff Performance - Dian Wahyuningsih (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The quality of human resources or employees can be known from their performance. Achieve high employee performance, it can be started from the employee's desire to be part of the company. the better the human capital and organizational culture, the better the employee's performance for the company. This study aims to determine how the condition of Human Capital, Organizational Culture, and Staff Performance at the Yogya Kepatihan Department Store. In addition, this study also aims to determine the magnitude of the influence of Human Capital, Organizational Culture on Staff Performance. A survey was conducted at the Yogya Kepatihan Department Store. The research method used is descriptive and verification with a quantitative approach. The data analysis method used is path analysis and hypothesis testing using the t-test and F-test which are processed using the SPSS Version 25 program. staff. Meanwhile, simultaneously Human Capital and Organizational Culture have a positive and significant effect on Staff Performance at the Yogya Kepatihan Department Store.